2019
DOI: 10.2139/ssrn.3498843
|View full text |Cite
|
Sign up to set email alerts
|

Banks and Corporate Income Taxation: A Review

Abstract: In this paper, I review the empirical literature in the intersection of banks and corporate income taxation that emerged over the last two decades. To structure the included studies, I use a stakeholder approach and outline how corporate income taxation plays into the relation of banks and their four main stakeholders: bank regulators, customers, investors and tax authorities. My contribution to the literature is threefold: First, I contribute by providing, to the best of my knowledge, a first comprehensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…An increase in interest rates means that banks are able to shift the tax burden onto customers. A review of various empirical studies by Gawehn (2020) agrees with this finding: corporate income taxation has an impact on banks' pricing decisions, which leads to a higher tax burden on customers.…”
Section: Literature Reviewmentioning
confidence: 53%
“…An increase in interest rates means that banks are able to shift the tax burden onto customers. A review of various empirical studies by Gawehn (2020) agrees with this finding: corporate income taxation has an impact on banks' pricing decisions, which leads to a higher tax burden on customers.…”
Section: Literature Reviewmentioning
confidence: 53%
“…Corporations frequently remit corporate taxes in advance, in installments, or on the stipulated deadline in an effort to enhance their financial efficacy. Gawehn (2020) undertook a German-based study that aimed to explore the correlation between corporate income taxation and banks. The investigation revealed that taxes play an integral role in various key areas such as debt financing, tax incidence, organizational form choices, profit shifting, financial reporting transparency, and customers' tax avoidance.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%